2003
DOI: 10.1002/bse.358
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and social disclosure and data richness in the mining industry

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 20 publications
2
76
0
2
Order By: Relevance
“…Some companies indicated that they maintain a comprehensive communication with local communities, and that they have included in their yearly objectives the spreading of the new sustainable mining management certificate obtained (UNE 22480) and the presentation of the projected activities of the companies affecting the local community. The number of companies publishing environmental reports has grown during last years, and even though it has not yet been proofed that reporting has a direct effect on environmental performance (Peck and Sinding, 2003), it is undoubtedly an example of efforts made by companies to achieve a more sustainable behavior.…”
Section: Measuring the Environmental Behaviormentioning
confidence: 99%
“…Some companies indicated that they maintain a comprehensive communication with local communities, and that they have included in their yearly objectives the spreading of the new sustainable mining management certificate obtained (UNE 22480) and the presentation of the projected activities of the companies affecting the local community. The number of companies publishing environmental reports has grown during last years, and even though it has not yet been proofed that reporting has a direct effect on environmental performance (Peck and Sinding, 2003), it is undoubtedly an example of efforts made by companies to achieve a more sustainable behavior.…”
Section: Measuring the Environmental Behaviormentioning
confidence: 99%
“…Existing research deals with trends and the evolving maturity of reporting practices, i.e. it seeks to ascertain progress in social, economic, governance or environmental performance disclosure at various levels (Coetzee and van Staden, 2011;Deloitte, 2007;Fonseca, 2010;Lins and Horwitz, 2007;Peck and Sinding, 2003;Perez and Sanchez, 2009;Tsang et al, 2009) or targets social and environmental disclosure as part of the CSR agenda (e.g. Jenkins, 2004;Jenkins and Yakovleva, 2006;Vintró et al, 2012).…”
Section: Gri Reporting In Mining and The Issue Of Data Qualitymentioning
confidence: 99%
“…Lastly, a high level of variation in social and environmental disclosure for global mining companies was reported by Jenkins and Yakovleva [43]. Peck and Sinding also indicated that there are even wide variances within a single industry in the reporting process for environmental performance [102]. With regard to social and environmental reporting practice specifically by Australian companies, Dong et al found in 2014 that disclosure of mining companies is quite narrow and limited in extent and non-quantitative which can lead to reduced investor confidence [96].…”
Section: Discussionmentioning
confidence: 98%